Leaf anatomy and macro-morphological data support a new species of the legume genus Chamaecrista (Fabaceae, Caesalpinioideae) from Goiás, Brazil - Matos, Ramon Guedes; Souza, Alessandro Oliveira De; Santos, Igor Soares; Silva, Marcos José Da (Phytotaxa, 2020)
Analysis of Brazilian collections and foreign herbaria, specially of those from the Midwest region of Brazil for taxonomic studies on Chamaecrista sect. Absus subsect. Absus developed by the authors, resulted in a discover a new species. Chamaecrista barnebyana is here described, illustrated, and commented on its distribution, conservation assessment, including environmental preferences, flowering and fruiting, and position systematic. Additionally, it is compared with morphologically similar species using macro-morphological and foliar anatomy characteristics.